Afscheid vertrekkende raadsleden. V.l.n.r.: Rotmeyer, v.d. Pols, ?, Ravesteyn. Beide laatsten zijn D'66-ers - Sonneveldt, Ton,
Afscheid vertrekkende raadsleden. V.l.n.r.: Rotmeyer, v.d. Pols, ?, Ravesteyn. Beide laatsten zijn D'66-ers.